The application of organic materials used in IC advanced packaging:A review - Liu Jikang (Memories - Materials, Devices, Circuits and Systems)
With the development of advanced technologies, the importance of semiconductor packaging has been further highlighted. To meet the increasing complexity and performance requirements of semiconductor devices, many integrated circuit (IC) advanced packaging technologies have been developed, which including flip chip (FC), bumping, fan-in wafer level packaging (FIWLP), fan-out wafer level packaging (FOWLP), 2.5D packaging (interposer), CMOS image sensor through silicon via (CIS-TSV), fan-out panel level packaging (FOPLP) and so on. During the manufacturing process of those IC advanced packaging technologies, many organic materials including photoresist (PR), photosensitive polyimide (PSPI), underfill, epoxy molding compound (EMC), temporary bonding adhesive, high temperature bonding adhesive, dry film and printing ink have been applied. In this paper, we described the application of organic materials including PR, PSPI, underfill, EMC, temporary bonding adhesive, high temperature bonding adhesive, dry film and printing ink used in the IC advanced packaging.